Characterization and prediction of issue-related risks in software projects - Choetkiertikul, M.; Dam, H.; Tran, The Truyen; Ghose, A. (2015)
© 2015 IEEE. Identifying risks relevant to a software project and planning measures to deal with them are critical to the success of the project. Current practices in risk assessment mostly rely on high-level, generic guidance or the subjective judgements of experts. In this paper, we propose a novel approach to risk assessment using historical data associated with a software project. Specifically, our approach identifies patterns of past events that caused project delays, and uses this knowledge to identify risks in the current state of the project. A set of risk factors characterizing 'risky' software tasks (in the form of issues) were extracted from five open source projects: Apache, Duraspace, JBoss, Moodle, and Spring. In addition, we performed feature selection using a sparse logistic regression model to select risk factors with good discriminative power. Based on these risk factors, we built predictive models to predict if an issue will cause a project delay. Our predictive models are able to predict both the risk impact (i.e. The extend of the delay) and the likelihood of a risk occurring. The evaluation results demonstrate the effectiveness of our predictive models, achieving on average 48% - 81% precision, 23% - 90% recall, 29% - 71% F-measure, and 70% - 92% Area Under the ROC Curve. Our predictive models also have low error rates: 0.39 - 0.75 for Macro-averaged Mean Cost-Error and 0.7 - 1.2 for Macro-averaged Mean Absolute Error.